Development of PolyQuest educational game using Construct 3 to stimulate students' learning interest in polynomials - Ahmad Faizun; Elsa Komala; Sarah Inayah; Md. Fajlay Rabbi (Universitas Sarjanawiyata Tamansiswa, 2026)
Interest in learning mathematics is an important factor influencing students' success in understanding mathematical concepts. In the digital era, technological advancements provide opportunities to create interactive and engaging learning experiences through digital media. This study aimed to develop the PolyQuest Educational Game using Construct 3 as a digital learning medium to stimulate students' interest in learning polynomial concepts. The study employed the Research and Development method with the ADDIE model, comprising the Analyze, Design, Develop, Implement, and Evaluate stages. The product was evaluated through expert validation and a preliminary small-scale classroom trial involving two mathematics teachers and eight eleventh-grade students from a senior high school in Cianjur, who were selected through purposive sampling. Data were collected using expert validation sheets, practicality questionnaires, and a students' learning-interest questionnaire, and were analyzed descriptively using a five-point Likert scale. PolyQuest obtained a mean validity score of 91%, derived from material validation (90%) and media validation (92%), a practicality score of 96%, and a mean learning-interest score of 93%, all of which fall into the highest category of the assessment criteria. These findings indicate that PolyQuest is a valid and practical learning medium with the potential to foster students' interest in learning mathematics, although its effectiveness still requires confirmation through larger-scale field testing. This study contributes a Construct 3-based platformer game that embeds polynomial problem-solving, progressive levels, and immediate feedback within a single learning environment, thereby offering teachers a ready-to-use medium and developers a design reference for senior high school mathematics.